Suomalaisen urheiludiplomatian "pelikirja"? Sisällönanalyysi urheiludiplomatian strategioista viestinnässä ja asiakirjoissa - Hammar, Hanna (2025)
Hammar, H. 2025. The” Playbook” of Finnish Sports Diplomacy? Content analysis of sports diplomatic strategies in communication and documents. Faculty of Sports and Health Sciences, University of Jyväskylä, Master’s thesis of Social Sciences of Sports, 2025 62 pages, 3 attachments.